Кераміка трипільської культури з енеолітичного поселення в с. Зимне - Позіховський, Олександр (Muzeum Okręgowe w Rzeszowie, 2019)
With reference to the literature on the subject, there is a discussion on the chronological affiliation of the ceramics of the Trypillian culture from the site in Zimne. Belonging to individual groups is also considered. Lack of full publication presenting ceramics with such characteristics makes it difficult to explain this issue. Therefore, it is necessary to publish the complete collection of the Trypillian culture coming from this site.

The studies on the multicultural site in Zimne (near Włodzimierz Wołyński) have brought the discovery of, among others, ceramics from the Trypillian culture. Their importance in the context of broader research issues prompted the author to publish these artefacts. A detailed analysis of technological features, morphology and ornamentation has been presented in a broadly comparative context. The issues of belonging of these materials to the Gorodosk and Brynzeny groups, as well as their relationships with the Funnel Beaker culture have been discussed extensively. Moreover, extremely interesting arguments in this discussion have been also supplemented by C14 dates recently obtained for 12 samples from the site in Zimne.
Ceramic materials of the Trypillian culture from the eneolithic site in Zimne
Keywords: Trypillian culture; Gorodosk group; Brynzeny group; Funnel Beaker culture